2017
DOI: 10.1038/s41598-017-00930-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fitc-Labeled Igy Antibody: Fluorescence Imaging Toxoplasma Gondii In Vitro

Abstract: Toxoplasmosis is caused by T. gondii and can create serious health problems in humans and also worldwide economic harm. Because of the clinical and veterinary importance of toxoplasmosis, its timely and accurate diagnosis has a major impact on disease-fighting strategies. T. gondii surface antigen 1 (SAG1), an immunodominant-specific antigen, is often used as a diagnostic tool. Therefore, the aim of this study was the optimization of novel fluorescein isothiocyanate (FITC) labeling of the SAG1-specific IgY ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…Therefore, this study revealed a potential diagnostic test for toxoplasmosis. More recently, Anti-SAG1 IgY conjugated to fluorescein isothiocyanate detected T. gondii tachyzoites in a colony, by means of immunofluorescence, and may be used to detect the protozoan in other types of samples [114].…”
Section: Parasitic Infections Diagnosismentioning
confidence: 99%
“…Therefore, this study revealed a potential diagnostic test for toxoplasmosis. More recently, Anti-SAG1 IgY conjugated to fluorescein isothiocyanate detected T. gondii tachyzoites in a colony, by means of immunofluorescence, and may be used to detect the protozoan in other types of samples [114].…”
Section: Parasitic Infections Diagnosismentioning
confidence: 99%
“…Similar ascertainment was recently reported by Sert et al . in using a fluorescein isothiocyanate (FITC) labeling of the SAG1-specific chicken egg yolk antibody (IgY) to show the potential for immunofluorescence imaging of T. gondii in vitro [54]. Therefore, the recombinant conjugate scFvSG15(V L T8P)-AP presented here has the potential to be used as diagnostic tools to confirm the presence of T. gondii parasites in biological samples by means of direct immunofluorescence assay.…”
Section: Discussionmentioning
confidence: 99%
“…This dye, the molecular formula of which is C 21 H 11 NO 5 S, causes a green fluorescence; it bonds covalently to biomolecules via the NCS functional group and has a high quantum yield [15,16]. The maximums of the absorption and fluorescence wavelengths are 495 and 520 nm, respectively [17]; owing to this, the background fluorescence of biological specimens is reduced to the minimum.…”
Section: Applied Opticsmentioning
confidence: 99%